2014
DOI: 10.1002/pon.3701
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers' involvement in caring for a hospitalized patient with cancer and their quality of life in a country with strong family bonds

Abstract: Our findings identified modifiable factors such as dealing with psychological issues and lack of experience in caring that negatively influenced the QoL of family caregivers. These factors are potential targets for intervention strategies. Education and intervention programs focusing on dealing with psychological problems in cancer care might improve the QoL of both patients and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 33 publications
4
79
1
6
Order By: Relevance
“…Through our review we identified 27 citations that dealt with NCD management at the structural policy level [25, 61, 88], clinical level [23, 54, 63, 72, 75, 83, 9092, 95, 106, 108, 110, 113], community [16, 38, 52, 73, 74, 100], family [105, 107], and individual level [59, 77]. At the structural level, we recognized three issues: health insurance services for NCD patients [88], the need for a better collaboration between health and registration sectors [61], and the need to address the double burden of NCDs and infectious diseases such as tuberculosis and diabetes [25], which might be aggravated by smoking [39].…”
Section: Resultsmentioning
confidence: 99%
“…Through our review we identified 27 citations that dealt with NCD management at the structural policy level [25, 61, 88], clinical level [23, 54, 63, 72, 75, 83, 9092, 95, 106, 108, 110, 113], community [16, 38, 52, 73, 74, 100], family [105, 107], and individual level [59, 77]. At the structural level, we recognized three issues: health insurance services for NCD patients [88], the need for a better collaboration between health and registration sectors [61], and the need to address the double burden of NCDs and infectious diseases such as tuberculosis and diabetes [25], which might be aggravated by smoking [39].…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the aforementioned studies were in line with the OECD reports 'Education at a Glance' which suggested positive influence of education on life satisfaction (OECD, 2011) and physical health (OECD, 2014). However, in the two recent studies about Indonesian caregivers (Effendy et al, 2014) and Chinese caregivers (Yang et al, 2012), educational preparation of caregivers was not a significant contributor of their quality of life. Whether different socioeconomical background accounted for incongruent results requires further study.…”
Section: Rangementioning
confidence: 93%
“…Perbedaan tingkat stress ini dapat terjadi karena budaya dan status hubungan pelaku rawat dengan kliennya. Masyarakat di Indonesia dikenal memiliki hubungan kekeluargaan yang kuat (Effendy et al, 2015). Hal ini akan bermakna pada dukungan sosial.…”
Section: Pembahasanunclassified